Fecal microbiota transplantation: application scenarios, efficacy prediction, and factors impacting donor-recipient interplay - Liu, Yaxin; Li, Xinru; Chen, Yuchao; Yao, Qinyan; Zhou, Jinjie; Wang, Xiaoxuan; Meng, Qingguo; Ji, Jiaxuan; Yu, Zihan; Chen, Xin (Frontiers in Microbiology, 2025)
Fecal microbiota transplantation (FMT) represents a therapeutic approach that directly regulates the gut microbiota of recipients, normalizes its composition and reaping therapeutic rewards. Currently, in addition to its general application in treating Clostridium difficile (C. difficile) infection (CDI), FMT treatment has also been extended to the fields of other gastrointestinal diseases, infections, gut-liver or gut-brain axis disorders, metabolic diseases and cancer, etc. Prior to FMT, rigorous donor screening is essential to reduce the occurrence of adverse events. In addition, it is imperative to evaluate whether the recipient can safely and effectively undergo FMT treatment. However, the efficacy of FMT is influenced by the complex interactions between the gut microbiota of donor and recipient, the degree of donor microbiota engraftment is not necessarily positively related with the success rate of FMT. Furthermore, an increasing number of novel factors affecting FMT outcomes are being identified in recent clinical trials and animal experiments, broadening our understanding of FMT treatment. This article provides a comprehensive review of the application scenarios of FMT, the factors influencing the safety and efficacy of FMT from the aspects of both the donors and the recipients, and summarizes how these emerging novel regulatory factors can be combined to predict the clinical outcomes of patients undergoing FMT.